2020
DOI: 10.1002/prs.12144
|View full text |Cite
|
Sign up to set email alerts
|

Construction method and application of real‐time monitoring and early‐warning model for anaerobic reactor leakage

Abstract: The anaerobic reactor is one of the most critical reaction devices for biogas engineering, wherein is usually a large amount of flammable gas methane. Fire and explosion accidents will be easily triggered if the gas leaks, threatening the surrounding buildings, equipment, personnel, and so forth. Avoiding the significant accidents caused by CH 4 leakage has become a critical issue in the design and condition monitoring for an anaerobic reactor. This article presents a model construction method for leakage earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Methane in digesters is flammable and harmful when openly released into the atmosphere. The study by Feng Wang [ 124 ] demonstrated that simulation data from the Unified Dispersion Model can be used to develop an empirical model for predicting the effects of gas leakage. A real-time monitoring early-warning system was developed to prevent accidents and ensure safety using an incident database, hazard and operability analysis (HAZOP) analysis, numerical simulation, consequence quantitative calculation, and emergency response guidance.…”
Section: Resultsmentioning
confidence: 99%
“…Methane in digesters is flammable and harmful when openly released into the atmosphere. The study by Feng Wang [ 124 ] demonstrated that simulation data from the Unified Dispersion Model can be used to develop an empirical model for predicting the effects of gas leakage. A real-time monitoring early-warning system was developed to prevent accidents and ensure safety using an incident database, hazard and operability analysis (HAZOP) analysis, numerical simulation, consequence quantitative calculation, and emergency response guidance.…”
Section: Resultsmentioning
confidence: 99%
“…CO 2 geological utilization is currently the most widely promoted and economically beneficial technique. It includes CCUS-EOR and CUS-ECBM (enhanced coal bed methane) technologies. , Among them, CCUS-EOR technology has undergone large-scale engineering demonstration stages and has achieved positive application results in oilfields such as Daqing, Jilin, Jiangsu, Shengli, and Huadong Oil and Gas Company, holding dual significance in guaranteeing national energy security and protecting the ecological environment. Physical utilization of CO 2 primarily refers to its applications in the food industry, such as producing carbonated beverages, deoxygenated water, dairy products, and food preservation. In chemical utilization, CO 2 can serve as a raw material for the synthesis of various chemical products, including urea, ammonium bicarbonate, dimethyl carbonate, polycarbonates, methane, synthesis gas, methanol, polyurethane, and salicylic acid. , In the context of biological utilization, CO 2 can promote the photosynthesis of crops, transform into food and feed, and be utilized in synthesizing pharmaceuticals, health products, and chemical raw materials, presenting extensive commercial prospects.…”
Section: A Bibliometric Review Of Global Progress In Ccus Technology ...mentioning
confidence: 99%
“…Fluid mechanics has been considered in various studies to address the dynamic characteristics and continuing processes in construction projects due to its flexibility and accuracy in fluid (uncertainty) simulations and quantitative predictions. In fact, this method has been effective for solving problems in diverse domains (Mishra, 2015;Seminara et al, 2020), such as traffic transportation (Lighthill and Whitham, 1955;Richards, 1956), ecology (Jones et al, 2018), supply chain inventory analysis (Kachani and Perakis, 2006), and manufacturing systems (Wiendahl et al, 2002;Efthymiou et al, 2009). These studies have provided insights into dynamic phenomena that exhibit characteristics similar to those of fluid mechanics.…”
Section: Application Of Fd To Alternate Domainsmentioning
confidence: 99%
“…Pedestrian movement studies have also adopted FD analogies as a foundation for modeling (Qiu et al, 2018;Sun, 2018). FD models have been utilized in an ecological context to estimate species movement rates across terrestrial landscapes (Feliciani and Nishinari, 2018), supply chain inventory analysis (Kachani and Perakis, 2006), and manufacturing systems (Wiendahl et al, 2002;Efthymiou et al, 2009). These examples illustrate the versatility and effectiveness of applying mathematical models and theories to domains outside the one in which they were established.…”
Section: Application Of Fd To Alternate Domainsmentioning
confidence: 99%